Diabetes Awareness and Acceptance in Patients with Type 2 Diabetes: A Single-Center Cross-Sectional Study in Istanbul, Türkiye - Hatice Tursun; Arzu Erkoç (Healthcare, 2026)
Objectives: Diabetes continues to be a major and increasingly prevalent public health problem both globally and in Türkiye. Effective management of type 2 diabetes (T2D) largely depends on individuals’ ability to sustain daily self-management behaviors. This study was conducted to determine diabetes awareness and disease acceptance among hospitalized adults with T2D receiving care at a tertiary hospital in Istanbul, Türkiye, and to examine the sociodemographic and clinical factors associated with these levels. Methods: A descriptive, cross-sectional, and correlational design was used in accordance with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines. The sample consisted of 118 patients selected using purposive consecutive sampling. Data were collected using the Diabetes Awareness and Acceptance Scale (DAAS). Results: The mean DAAS total score was 84.08 ± 12.02. Regular medication adherence, dietary adherence, and consistent attendance at diabetes follow-up visits were associated with higher awareness and acceptance levels. In the hierarchical multiple regression analysis, regular attendance at follow-up visits and dietary adherence remained independently associated with higher DAAS scores after adjustment for the other variables. Conclusions: This study provides descriptive evidence regarding diabetes awareness and acceptance among hospitalized adults with T2D. Higher DAAS scores were independently associated with regular attendance at diabetes follow-up visits and adherence to dietary recommendations. These findings indicate that engagement in recommended diabetes care behaviors is associated with diabetes awareness and acceptance. However, the findings should be interpreted in the context of hospitalized patients from a single tertiary-care center and may not be generalizable to all individuals with T2D in Türkiye.